Monitoring Epiphytic Lichen Biodiversity to Detect Environmental Quality and Air Pollution: the Case Study of Roccamonfina Park (Campania Region - Italy) - G., Aprile G.; I., Catalano; A., Migliozzi; A., Mingo (IntechOpen, 2011)
None